Himalayan fermented foods : microbiology, nutrition, and ethnic values - Tamang, Jyoti Prakash (Boca Raton, Florida : CRC Press, 2010)
Catalogs the wide array of extensively studied fermented items found in the Himalayas, including fermented fish and vegetables. This book isolates, characterizes, and identifies each probiotic microorganism based on modern phenotypic and genotypic characteristics.
1. The Himalayas and food culture -- 2. Fermented vegetables -- 3. Fermented legumes -- 4. Fermented milks -- 5. Fermented cereals -- 6. Ethnic fish products -- 7. Ethnic meat products -- 8. Ethnic starters and alcoholic beverages -- 9. Antiquity and ethnic values -- 10. Prospects of the Himalayan fermented foods
Includes bibliographical references and index
Keywords: Fermented foods -- Himalaya Mountains Region